2013
DOI: 10.1055/s-0033-1343833
|View full text |Cite
|
Sign up to set email alerts
|

Total Lower Lip Reconstruction Using Free Neurotendinofasciocutaneous Anterolateral Thigh Composite Flap: A Case Report

Abstract: Total lower lip reconstructions are challenging procedures because of poor aesthetic and functional outcomes and limited availability of donor tissues that anatomically imitate the lip. We hereby report the free neurotendinofasciocutaneous anterolateral thigh composite flap as a new reconstructive option. A 48-year-old man presenting with a squamous cell carcinoma of the lower lip underwent wide resection of tumor, bilateral neck dissection, and lower lip reconstruction with the mentioned flap where the latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The ALT flap is an alternative option for lip reconstruction with the advantages of a 2-team approach, large skin paddle, chimeric and composite flap design, long and caliber vascular pedicle, inconspicuous donor-site scar, and sensate planning. 8,10,[33][34][35][36] However, variations in the vascular perforators of the skin paddle, 8,35,36 bulky skin paddle, 8,14,36 hairy vestibular lining in hirsute patient, 8 and color mismatch 8,36 are disadvantages of lip reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The ALT flap is an alternative option for lip reconstruction with the advantages of a 2-team approach, large skin paddle, chimeric and composite flap design, long and caliber vascular pedicle, inconspicuous donor-site scar, and sensate planning. 8,10,[33][34][35][36] However, variations in the vascular perforators of the skin paddle, 8,35,36 bulky skin paddle, 8,14,36 hairy vestibular lining in hirsute patient, 8 and color mismatch 8,36 are disadvantages of lip reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for oral reconstruction by improving free flaps have been reported. Chien and Onder used the ALT flap for the reconstruction of lip defects [ 14 , 15 ]. Reconstruction of midface defects through RFFF was described by Wei [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This flap is very versatile and can be trimmed and defatted to suit any type of defect. 5,[10][11][12] The FL can be used as an anchoring structure, similar to the PL tendon previously described. If this flap is not available, the second option is the PAP flap.…”
Section: Table 5 Algorithm For Extensive Lower Lip Defect Reconstructionmentioning
confidence: 99%
“…Several other techniques have also been reported for lower lip reconstruction. Composite anterolateral thigh (ALT) free flap and FL offer a good alternative, significantly reducing donor site morbidity 10–12 . Various authors have reported successful functional outcomes using free functioning muscle transfers 13–15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation